Starch-based hard carbon material as well as preparation method and application thereof

By carbonizing and pore formation after mixing preoxidized starch and polymer, the problems of complex process and starch foam agglomeration in the preparation of starch-based hard carbon materials are solved, and the good spherical structure of hard carbon materials and the efficient performance of sodium ion batteries are achieved.

CN119774579AActive Publication Date: 2025-04-08GUANGDONG UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411889619.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-08
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing methods and processes for preparing starch-based hard carbon composites are complex, and starch is prone to foaming and agglomeration during sintering, which affects the spherical structure of hard carbon materials and the first Coulomb efficiency of sodium ion batteries.

Method used

By carbonizing and pore formation after mixing preoxidized starch with a specific polymer (polypropylene or polyacrylonitrile), foaming and agglomeration of preoxidized starch is avoided, thereby maintaining a good spherical structure of hard carbon.

Benefits of technology

The first Coulomb efficiency of the sodium ion battery is improved, and the sodium ion battery made of this starch-based hard carbon material has good cycle stability and rate performance, while simplifying the process flow and improving industrial production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774579A_ABST
    Figure CN119774579A_ABST
Patent Text Reader

Abstract

The invention relates to a starch-based hard carbon material as well as a preparation method and application thereof, and the preparation method comprises the following steps: S1, performing pre-oxidation treatment on starch to obtain pre-oxidized starch; s2, mixing the pre-oxidized starch in the step S1 with a high-molecular polymer to obtain a mixture; s3, carbonizing the mixture to obtain a carbonized material; and S4, performing high-temperature pore forming on the carbonized material to obtain the starch-based hard carbon material. The high-molecular polymer is at least one of polypropylene or polyacrylonitrile. According to the preparation method, the pre-oxidized starch and the specific high-molecular polymer are mixed and then carbonized and pore-formed, so that the phenomena of foaming and agglomeration of the pre-oxidized starch can be effectively avoided, the obtained hard carbon keeps a good spherical structure, and the first coulombic efficiency of the sodium ion battery is further improved. Meanwhile, the sodium ion battery prepared from the starch-based hard carbon material also has good cycling stability and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery negative electrode materials, and more specifically, to a starch-based hard carbon material and a preparation method and application thereof. Background Art

[0002] With the research and development of sodium-ion batteries, hard carbon has received extensive attention as a new type of negative electrode material. Hard carbon is abundant in source and cheap in price. It has higher lithium storage capacity and excellent rate performance than the graphite negative electrode of lithium-ion batteries, and is the most commercially promising negative electrode material for sodium-ion batteries. Hard carbon is called a "house of cards structure", which is a disordered amorphous structure composed of a large number of disordered graphite crystallites and amorphous regions, which allows more defects and micropores in hard carbon materials to provide more active sodium storage sites.

[0003] Various biomass materials are used to prepare precursors of hard carbon materials. Among them, starch particles have a special spherical structure and can be used to prepare spherical hard carbon materials. Spherical hard carbon materials have high mechanical strength, high packing density, and low surface area to volume ratio. Starch has become a very competitive candidate for preparing hard carbon materials. However, starch is prone to foaming and agglomeration during the sintering process, so spherical hard carbon materials cannot be obtained, which in turn affects the first coulomb efficiency.

[0004] China's patented starch-based hard carbon negative electrode material preparation method, negative electrode material and sodium ion battery use linear heating to pretreat starch and perform esterification reaction during the pretreatment process, but there is a problem that some unesterified starch is very easy to gelatinize and agglomerate, making it difficult to maintain a good spherical structure.

[0005] The Chinese patent is a method for preparing corn starch-based hard carbon sodium ion battery negative electrode materials. The starch is treated with a cross-linking agent and a pore-forming agent, and the process includes three steps: cross-linking, alcohol washing and drying. During cross-linking, the pH needs to be adjusted and the material needs to be frozen overnight. The process is complicated and seriously affects industrial production efficiency.

[0006] Therefore, the existing methods for preparing starch-based hard carbon composites have complex process flows and the starch is prone to foaming and agglomeration during the sintering process, which to a large extent restricts the practical application development of starch as a hard carbon material. Summary of the invention

[0007] The primary purpose of the present invention is to overcome the problems of complex process flow and easy foaming and agglomeration of starch during sintering in the above-mentioned existing methods for preparing starch-based hard carbon composite materials, and to provide a method for preparing starch-based hard carbon materials. This preparation method can effectively avoid the foaming and agglomeration of pre-oxidized starch by mixing pre-oxidized starch and a specific high molecular polymer (polypropylene or polyacrylonitrile) and then carbonizing and forming pores, so that the obtained hard carbon maintains a good spherical structure, thereby improving the first coulombic efficiency of the sodium ion battery. At the same time, the sodium ion battery made of the starch-based hard carbon material also has good cycle stability and rate performance.

[0008] A further object of the present invention is to provide a starch-based hard carbon material.

[0009] Another object of the present invention is to provide the use of the above-mentioned starch-based hard carbon material in preparing a negative electrode for a sodium ion battery.

[0010] Another object of the present invention is to provide a negative electrode for a sodium ion battery.

[0011] Another object of the present invention is to provide a sodium ion battery.

[0012] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0013] A method for preparing a starch-based hard carbon material comprises the following steps:

[0014] S1. The starch is pre-oxidized to obtain pre-oxidized starch;

[0015] S2. The pre-oxidized starch and the polymer in step S1 are mixed to obtain a mixture;

[0016] S3. carbonizing the mixture to obtain a carbonized material;

[0017] S4. The carbonized material is subjected to high temperature pore formation to obtain the starch-based hard carbon material;

[0018] The high molecular polymer is at least one of polypropylene or polyacrylonitrile.

[0019] The inventors of the present invention have found through research that carbonization and pore formation after pre-oxidized starch and a specific polymer (polypropylene or polyacrylonitrile) are mixed can effectively avoid the foaming and agglomeration of pre-oxidized starch, so that the obtained hard carbon maintains a good spherical structure, thereby improving the first coulombic efficiency of the sodium ion battery. The reason may be that the carbon skeleton formed by the polymer during carbonization inhibits the aggregation of pre-oxidized starch. At the same time, the sodium ion battery made of the starch-based hard carbon material also has good cycle stability and rate performance.

[0020] Preferably, in step S1, the starch is at least one of corn starch, tapioca starch or sweet potato starch.

[0021] Preferably, in step S1, the temperature of the pre-oxidation treatment is 200-240°C.

[0022] Preferably, in step S1, the pre-oxidation treatment time is 12 to 18 hours.

[0023] Preferably, in step S2, the mass ratio of the pre-oxidized starch to the high molecular polymer is 5:(1-5).

[0024] More preferably, in step S2, the polymer is polypropylene, and the mass ratio of the pre-oxidized starch to the polymer is 5:(1-2.5). Within this mass ratio range, the sodium ion battery made of starch-based hard carbon material has a higher first coulombic efficiency.

[0025] More preferably, in step S2, the high molecular polymer is polyacrylonitrile, and the mass ratio of the pre-oxidized starch to the high molecular polymer is 5:(2.5-5). Within this mass ratio range, the sodium ion battery made of starch-based hard carbon material has a higher first coulombic efficiency.

[0026] Preferably, in step S2, the high molecular polymer is in powder form.

[0027] Preferably, in step S2, the number average molecular weight of the high molecular weight polymer is 40,000-60,000.

[0028] Preferably, in step S3, the carbonization temperature is 400-700°C

[0029] Preferably, in step S3, the carbonization time is 2 to 4 hours.

[0030] Preferably, in step S3, grinding is further included after carbonization.

[0031] More preferably, in step S3, the grinding method is manual grinding, and the grinding time is 10 to 20 minutes.

[0032] Preferably, in step S4, the high-temperature pore-forming process is: in an inert atmosphere, the temperature is raised from 30°C to 500-600°C and kept for 0.5-2h, then raised to 800-1000°C and kept for 0.5-2h, and finally raised to 1400-1500°C and kept for 0.5-2h.

[0033] More preferably, in step S4, the high-temperature pore-forming process is: in an inert atmosphere, the temperature is increased from 30°C to 500-600°C at a rate of 1-2°C / min and kept warm for 0.5-2h, then the temperature is increased to 800-1000°C at a rate of 1-2°C / min and kept warm for 0.5-2h, and finally the temperature is increased to 1400-1500°C at a rate of 1-2°C / min and kept warm for 0.5-2h.

[0034] More preferably, the inert atmosphere is one or both of nitrogen and argon.

[0035] The present invention also protects a starch-based hard carbon material, which is prepared by the above preparation method.

[0036] The application of the above-mentioned starch-based hard carbon material in preparing the negative electrode of a sodium ion battery is also within the protection scope of the present invention.

[0037] The present invention also protects a sodium ion battery negative electrode, which comprises the above-mentioned starch-based hard carbon material.

[0038] Preferably, the sodium ion battery negative electrode further includes a conductive agent, a binder and a current collector.

[0039] Preferably, the mass ratio of the starch-based hard carbon material, the conductive agent and the binder is (93-95): (1-3): (29-31).

[0040] More preferably, the binder is one or both of carboxymethyl cellulose and styrene-butadiene rubber latex.

[0041] Further preferably, the binder is carboxymethyl cellulose and styrene-butadiene rubber latex, and the mass ratio of carboxymethyl cellulose to styrene-butadiene rubber latex is 4:(25-27).

[0042] More preferably, the conductive agent is acetylene black.

[0043] More preferably, the current collector is copper foil.

[0044] The present invention also protects a sodium ion battery, which comprises the above-mentioned sodium ion battery negative electrode.

[0045] Preferably, the sodium ion battery further comprises a sodium ion battery positive electrode and a diaphragm electrolyte.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] The preparation method of the present invention can effectively avoid the foaming and agglomeration of the pre-oxidized starch by mixing the pre-oxidized starch with a specific high molecular polymer (polypropylene or polyacrylonitrile) and then carbonizing and forming pores, so that the obtained hard carbon can maintain a good spherical structure, thereby improving the first coulombic efficiency of the sodium ion battery. At the same time, the sodium ion battery made of the starch-based hard carbon material also has good cycle stability and rate performance.

[0048] In addition, the preparation method of the present invention has a simple process flow, which is conducive to improving the efficiency of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is the SEM image of the starch-based hard carbon material prepared in Example 3.

[0050] Figure 2 This is the SEM image of the starch-based hard carbon material prepared in Comparative Example 1.

[0051] Figure 3 The button battery made of starch-based hard carbon material prepared in Example 1 is 20-1500 mAg -1 Charge and discharge rate performance diagram under current density.

[0052] Figure 4 The button battery made of starch-based hard carbon material prepared in Example 2 is 20-1500 mAg -1 Charge and discharge rate performance diagram under current density.

[0053] Figure 5 The button battery made of starch-based hard carbon material prepared in Example 1 was charged at 300 mAg -1 Charge and discharge cycle performance diagram under current density. DETAILED DESCRIPTION

[0054] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0055] Example 1

[0056] This embodiment provides a method for preparing a starch-based hard carbon material, comprising the following steps:

[0057] 1) taking 10 g of corn starch and heating it from 25°C to 220°C at a rate of 2°C / min for 12 h in an air atmosphere to obtain pre-oxidized starch;

[0058] 2) mixing the pre-oxidized starch and polypropylene (number average molecular weight of 50,000) in step 1), and manually grinding for 40 minutes to obtain a mixture; wherein the mass ratio of the pre-oxidized starch to the polypropylene is 5:1;

[0059] 3) carbonizing the mixture, wherein the carbonization process is as follows: raising the temperature from 30°C to 600°C at 2°C / min under a nitrogen atmosphere, and keeping the temperature at 600°C for 3 hours; cooling to room temperature to obtain a carbonized material;

[0060] 4) The carbonized material was manually ground for 20 min, and then subjected to high-temperature pore making, and cooled to room temperature to obtain a starch-based hard carbon material; the high-temperature pore making process was as follows: in a nitrogen atmosphere, the temperature was increased from 30 °C to 600 °C at 2 °C / min and kept for 2 h, then the temperature was increased to 1000 °C at 2 °C / min and kept for 2 h, and finally the temperature was increased to 1500 °C at 2 °C / min and kept for 2 h.

[0061] Example 2

[0062] This embodiment provides a method for preparing a starch-based hard carbon material. The difference from Embodiment 1 is that polypropylene is replaced by polyacrylonitrile (number average molecular weight is 50,000).

[0063] Example 3

[0064] This embodiment provides a method for preparing a starch-based hard carbon material. The difference from Embodiment 1 is that the mass ratio of pre-oxygenated and pre-oxidized starch to polypropylene is 2:1.

[0065] Example 4

[0066] This embodiment provides a method for preparing a starch-based hard carbon material. The difference from Embodiment 1 is that the mass ratio of pre-oxygenated and pre-oxidized starch to polypropylene is 1:1.

[0067] Example 5

[0068] This embodiment provides a method for preparing a starch-based hard carbon material. The difference from Embodiment 2 is that the mass ratio of pre-oxygenated and pre-oxidized starch to polyacrylonitrile is 2:1.

[0069] Example 6

[0070] This embodiment provides a method for preparing a starch-based hard carbon material. The difference from Embodiment 2 is that the mass ratio of pre-oxygenated and pre-oxidized starch to polyacrylonitrile is 1:1.

[0071] Comparative Example 1

[0072] This comparative example provides a method for preparing a starch-based hard carbon material. Different from Example 1, no polypropylene is added.

[0073] Comparative Example 2

[0074] This comparative example provides a method for preparing a starch-based hard carbon material. The difference from Example 1 is that polypropylene is replaced by polyacrylic acid.

[0075] Characterization and performance testing

[0076] 1. SEM Characterization

[0077] The starch-based hard carbon materials prepared in Example 3 and Comparative Example 1 were characterized by SEM. Figure 1 This is the SEM image of the starch-based hard carbon material prepared in Example 3; Figure 2 This is the SEM image of the starch-based hard carbon material prepared in Comparative Example 1. Figures 1-2 It can be seen that the starch-based hard carbon material prepared in Example 1 presents a spherical structure; in Comparative Example 1, since no specific high molecular polymer is added, the starch foams and agglomerates during high temperature treatment (such as carbonization).

[0078] The SEM images of starch-based hard carbon materials prepared in other examples are similar to those in Example 3.

[0079] 2. Battery performance test

[0080] The starch-based hard carbon material prepared in each embodiment and comparative example was dissolved in deionized water with acetylene black, binder CMC, and styrene-butadiene rubber emulsion (BM451B) at a mass ratio of 94:2:4:26, mixed and stirred to obtain a slurry, and then the obtained slurry was coated on a copper foil and vacuum dried for 12 hours to obtain a negative electrode sheet. The battery was then assembled in an argon-filled glove box, with the negative electrode being the above-mentioned negative electrode sheet, the positive electrode being a sodium sheet, the diaphragm being glass fiber, and the electrolyte being a NaCF3SO3 solution. The assembled button cell was then subjected to an electrochemical performance test, and the results are as follows: Figures 3 to 5 And as shown in Table 1.

[0081] Table 1 shows the button batteries made of starch-based hard carbon materials obtained in various examples and comparative examples at 300 mAg -1 First coulombic efficiency at current density.

[0082] Table 1 Electrochemical performance test results

[0083] First coulombic efficiency / (%) Example 1 89.41 Example 2 86.83 Example 3 91.61 Example 4 84.79 Example 5 95.82 Example 6 92.11 Comparative Example 1 59.57 Comparative Example 2 73.26

[0084] As shown in Table 1, the button battery 300mAg made of starch-based hard carbon material prepared by the present invention -1 The first coulombic efficiency at the current density is above 84.79%.

[0085] Since no specific high molecular polymer was added in Comparative Example 1 and polyacrylic acid was used instead of the specific high molecular polymer in Comparative Example 2, the starch foamed and agglomerated during the high temperature treatment, which affected the initial coulombic efficiency.

[0086] Figures 3-4 The button batteries made of starch-based hard carbon materials prepared in Examples 1 and 2 are respectively 20 to 1500 mAg -1 Charge and discharge rate performance diagram under current density.

[0087] from Figure 3 It can be seen that the button battery made of starch-based hard carbon material prepared in Example 1 has good thermal conductivity at 20, 30, 60, 120, 240, 300, 600, 900 and 1500 mAg -1 The reversible capacities obtained at the current densities were 358, 183, 159, 126, 94, 87, 61, 52, and 41 mAg, respectively. -1 .

[0088] from Figure 4 It can be seen that the button battery made of starch-based hard carbon material prepared in Example 2 has good thermal conductivity at 20, 30, 60, 120, 240, 300, 600, 900 and 1500 mAg -1 The reversible capacities obtained at the current densities were 228, 162, 159, 141, 136, 124, 112, 102, and 68 mAg, respectively. -1 .

[0089] The rate performance of Examples 3 and 4 is similar to that of Example 1, and the rate performance of Examples 5 and 6 is similar to that of Example 2. The above results show that the button battery made of starch-based hard carbon material prepared by the present invention has good rate performance.

[0090] Figure 5 The starch-based hard carbon material prepared in Example 1 was used to make a button battery at 300 mAg -1 Charge and discharge cycle performance diagram under current density.

[0091] from Figure 5 It can be seen that at 300mAg -1 At the current density of 1.5, the reversible capacity of the starch-based hard carbon material prepared in Example 1 after 35 cycles was 138 mAg -1 The capacity retention rate is 45.15%. The cycle performance of other examples is similar to the result of Example 1. This shows that the starch-based hard carbon material prepared by the present invention has good cycle stability.

[0092] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a starch-based hard carbon material, characterized in that: The following steps are involved: S1. The starch is pre-oxidized to obtain pre-oxidized starch; S2. The pre-oxidized starch and the polymer in step S1 are mixed to obtain a mixture; S3. carbonizing the mixture to obtain a carbonized material; S4. The carbonized material is subjected to high temperature pore formation to obtain the starch-based hard carbon material; The high molecular polymer is at least one of polypropylene or polyacrylonitrile.

2. The preparation method according to claim 1, characterized in that: In step S1, the starch is at least one of corn starch, tapioca starch or sweet potato starch.

3. The preparation method according to claim 1, characterized in that: In step S1, the temperature of the pre-oxidation treatment is 200-240°C.

4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the pre-oxidized starch to the high molecular polymer is 5:(1-5).

5. The preparation method according to claim 1, characterized in that: In step S2, the number average molecular weight of the high molecular weight polymer is 40,000 to 60,000.

6. The preparation method according to claim 1, characterized in that: In step S3, the carbonization temperature is 400-700°C.

7. A starch-based hard carbon material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the starch-based hard carbon material according to claim 7 in preparing a negative electrode for a sodium ion battery.

9. A sodium ion battery negative electrode, characterized in that: The sodium ion battery negative electrode comprises the starch-based hard carbon material as described in claim 7 above.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery negative electrode as described in claim 9 above.

Citation Information

Patent Citations

  • Expanded graphite-based carbon composite material as well as preparation method and application thereof

    CN115448307A

  • Method for preparing hard carbon material from biomass material and high-molecular polymer, product and application

    CN118183687A

  • Preparation method of bulk hard carbon material

    CN118289734A

  • Heteroatom-doped porous hard carbon negative electrode material and preparation method and application thereof

    CN118289737A

  • Starch-based hard carbon material and gradient oxidation annealing preparation method and application thereof

    CN119038527A